A new earth eaudiobook The opportunity of our time. - Tolle, Eckhart (Penguin Audio, 2005)
OPRAH’S BOOK CLUB PICK 2025 #1 NEW YORK TIMES BESTSELLER “As we welcome a new year, I wanted to revisit the book that had more effect on me than any other book by a living author has had on my perception of how I understand my connection to the world.” —Oprah Winfrey (Oprah’s Book Club January 2025) With his bestselling spiritual guide The Power of Now , Eckhart Tolle inspired millions of readers to discover the freedom and joy of a life lived “in the now.” In A New Earth , Tolle expands on these powerful ideas to show how transcending our ego-based state of consciousness is not only essential to personal happiness, but also the key to ending conflict and suffering throughout the world. Tolle describes how our attachment to the ego creates the dysfunction that leads to anger, jealousy, and unhappiness, and shows readers how to awaken to a new state of consciousness and follow the path to a truly fulfilling existence. Illuminating, enlightening, and uplifting, A New Earth is a profoundly spiritual manifesto for a better way of life—and for building a better world.